Teknologi Tepat Guna Mesin Pencuci Porang untuk Meningkatkan Produktivitas Petani Porang di Desa Morang, Kare, Madiun: Indonesia - Irawaty, Wenny; Hadi; Wijaya, Christian Julius; Indrawati, Chatarina Dian; Anggorowati, Adriana Anteng; Soetaredjo, Felycia Edi; Santoso, Shella Permatasari; Ismadji, Suryadi; Yuliana, Maria; Ernest, Edward H; Wardhani, Rinda; Afendi, Yulius; Panjaitan, Imelda (UII, 2024)
Recently, the productivity of porang tuber-based products has been growing well, especially after the Indonesian Government released a policy to prohibit the export of porang plants and their harvested products. One of the porang-based products is in the form of chips. Before processing, the porang tubers must be washed thoroughly to remove soil/dirt from the surface. The conventional washing process of each tuber can take up to 3-5 minutes. Therefore, the purpose of this activity is to design and manufacture porang washing equipment based on centrifuge washing model with rubber vibration. Four stages to carried out the program, i.e. designed and manufactured the washing machine, run the machine in laboratory, training activities to the porang farmers, and evaluation process. From the observation to porang farmers as our partner during the activity, it can be seen that the partners can operate the washing machine well. The results show that the washing process of porang tuber using this technology can save the washing time up to 90% compared to the conventional washing. The surface cleanliness of porang tubers resulted from the developed washing machine is the same as the conventional one. The noise level of the machine has met the requirement of Indonesian Government. It is clear that the usage of the machine can increase the production capacity of products-based porang tuber. In addition, the use of this technology may promote a more comfortable and healthy work environment due to ergonomic reason, however, based on RULA analysis, the machine is still need to be improved in the future. Overall, the partners were satisfied with this activity and expected to have further programs in the future.